A COMPREHENSIVE EXPLORATION OF PUBLIC-PRIVATE PARTNERSHIP IN TOLL ROAD INFRASTRUCTURE DEVELOPMENT - Evy Steelyana Wiyarti; Dhea Kinanti (Jurnal Bisnis dan Akuntansi, 2024)
This study explores collaborative governance in Public-Private Partnership (PPP) based toll road development between 2000 and 2020. Analyzing articles from various academic journals, The majority of the articles were from Q1-ranked journals according to the SCImago Journal & Country Rank website. The research identified a rise in the number of publications on this topic, with 2015 showing the most. The most frequent research themes were risk management, value for money, and critical success factors for PPPs. Governance theory emerged as a key concept influencing PPPs in toll road development, alongside Institutional Theory and Stakeholders Theory within Public Sector Accounting Theory. Overall, the study highlights a growing interest in collaborative governance for PPPs and emphasizes the importance of effective collaboration and decision-making for successful PPP projects.